Perlindungan Hukum Bagi Konsumen Terhadap Peredaran Obat Kuat Secara Ilegal Melalui Media Online - Puspitasari, Intan; Haliwela, Nancy Silvana; Latupeirissa, Julianus Edwin (PATTIMURA Law Study Review, 2024)
ABSTRACT: Buying and selling activities through online media are widespread in Indonesia, resulting in the emergence of various negative impacts that can endanger consumer safety due to the circulation of illegal strong drug products, for this reason it is necessary to enforce the law and form legal accountability from business actors towards consumers due to the online distribution of strong drugs illegally via online media. This research aims to determine and explain law enforcement and forms of legal responsibility from business actors towards consumers as a result of the illegal distribution of strong drugs through online media. The type of research used in this writing is normative legal research. By using a statutory approach and a conceptual approach, the legal materials used are primary and secondary, collecting legal materials using library research, namely collecting relevant legal materials to obtain valid and accurate data, from all legal materials obtained, compiled systematically and then processed and analyzed in a normative juridical manner, namely describing the problems related to this research. The results of this research conclude that law enforcement through BPOM is intended to protect the rights of consumers who are harmed by consuming illegal strong drugs distributed through online media, from actions carried out by business actors, legal responsibility that can be sought from business actors is through administrative sanctions in accordance with regulations. in force, however administrative sanctions do not provide a deterrent effect for business actors. For this reason, regulations regarding the distribution of strong drugs through online media must be upgraded to law, so that criminal sanctions can be provided as a deterrent to business actors. BPOM also needs to collaborate with the National Cyber ​​Agency and Kominfo to make it easier to reach and block accounts selling illegal drugs, and the public needs to be educated about illegal drugs in online media, so that people have knowledge of the consequences of consuming drugs that endanger health and safety.